EFFECT OF APPLYING GROWTH REGULATORS ON YIELD AND FORMATION OF PRODUCTIVITY ELEMENTS OF SPRING BARLEY PLANTS IN THE CONDITIONS OF THE STEPPE ZONE OF UKRAINE - Ishchenko, V. A. (Scientific Progress & Innovations, 2021)
In the conditions of unstable moistening of the Northern Steppe, the necessity arises to study the application of Grain-active-C plant growth regulator in the technology of cultivating common spring barley of naked and chaffy types in the context of climate change. The comprehensive study and analysis of growth regulator application in resource-saving technology of common spring barley cultivation were conducted. On the plots where Grain-active-C preparation was used, the number of stems of Viking chaffy spring barley variety was higher as compared with the control variant by 27–71 pcs/m2 (6.1–16.1 %), of Cardinal naked variety – by 16–70 pcs/m2 (3.4–14.6 %). The crop yield of spring barley is determined by the number of productive stems per unit area and grain weight from one ear. In this case, the grain weight from one ear is directly dependent on grain content. The use of Grain-active-C plant growth regulator (PGR) for seed treatment and spraying of plants in the tillering phase had a positive effect on the individual productivity elements of spring barley plants. Larger grain weight of 1.12 and 1.03 g in the main ear, both of naked and chaffy varieties was formed in the variant of seed treatment and spraying crops with Grain-active-C in the tillering phase. The complex use of Grain-active-C PGR, the active substance of which is a biologically active organic compound well-soluble in water, the structure of which is close to the structure of protein substance, contains a large number of nitrogen atoms and has fungicidal and bactericidal properties for seed treatment and spraying crops of chaffy and naked spring barley, which ensured a significant increase in crop yield – by 0.68 t/ha and 0.52 t/ha (15.3 and 13.2 %).The results of experimental studies determine the expediency of using Grain-active C growth regulator for pre-sowing seed treatment and spraying crops in the tillering phase in order to increase the resistance of common spring barley plants to extreme growing conditions and increase yields. The obtained results confirmed the prospects of using Grain-active-C PGR in resource-saving technology of cultivating chaffy and naked spring barley varieties in the Steppe zone of Ukraine.